Propagação e conservação ex situ de Melocactus sergipensis (Cactaceae), espécie endêmica e criticamente ameaçada de extinção - Bravo Filho, Eronides Soares (2019)
The Cactaceae family is monophyletic, botanically distributed in 127 genera, approximately 1500 species and subdivided into four subfamilies: Maihuenoideae, Pereskeoideae, Opuntioideae and Cactoideae. Typical of the American continent and occur in climate, soil and diverse ecosystems. The genus Melocactus, known as head-of-monkey, is composed of 38 species, distributed from Central America, the Caribbean, Andes, Amazonia, Roraima, Espirito Santos, Minas Gerais, Rio de Janeiro and Northeast Brazil. The Caatinga biome presents the highest population density of this genus, a feature that makes Brazil the world center of diversity. The Melocactus sergipensis discovered in 2014 in the state of Sergipe is currently the only endemic species of Cactaceae in the state and is critically endangered (CR). The objective of this research was to establish a protocol for seed germination, micropropagation, acclimatization and ex situ conservation of M. sergipensis. Seed germination experiments were performed in a completely randomized design (DIC), with three treatments (control, seeds soaked for six hours and seeds soaked for six hours in water solution + 2 mg L -1 of gibberellin), 25 replicates with two seeds per experimental unit in vitro, already in greenhouse the experiment was composed of five replicates with 10 seeds per experimental unit. Four treatments were used (Caatinga soil, Franco siltoso soil, vegetal soil, washed sand + 1:1 vegetal soil), five replications, with five plants per experimental unit. The evaluated variables were percentage of germination, germination speed index, survival percentage, stem height, stem diameter, fresh matter weight and radicle length. Already, the micropropagation experiment was installed in a completely randomized design, composed of four treatments, 10 replicates and the experimental unit was composed by one explant. The nutrient medium was ½ MS supplemented with 30 g L-1 of sucrose and 7 g L-1 of agar and concentrations of phormons: BAP (0,0; 1,5; 3,0 and 6,0 mg L-1), ANA (0,0; 1,5; 3,0 and 6,0 mg L-1) and combining BAP/ ANA (0,0; 1,0/0,5; 2,0/1,0 and 4,0/2,0 mg L-1). The data were submitted to analysis of variance and the means were compared by the Tukey test, 5% of significance. Soaking for six hours with and without gibberellin at 2 mg L-1 significantly increased in vitro germination. In greenhouse did not differentiate significantly and presented germination above 80% in all treatments. In the acclimatization phase of the plants obtained through seed germination, the survival index varied from 88% (vegetal soil + sand washed 1:1) to 100% (Caatinga soil), the soil substrate Franco siltoso in general presented the best results. Balanced supplementation of BAP/ANA in the nutrient medium at the ratio of 1,0/0,5 mg L-1 provided a higher number of budding during the multiplication phase. In the acclimatization of M. sergipensis shoots obtained in the micropropagation 70% of the post-transplant shoots survived for the substrate. Field conservation presented a survival rate of only 20%.